Biomechanical Comparison of Intramedullary Screw Versus Low-Profile Plate Fixation of a Jones Fracture. (April 2016) - Huh, Jeannie; Glisson, Richard R.; Matsumoto, Takumi; Easley, Mark E.
Background: Intramedullary screw fixation of fifth metatarsal Jones fractures often produces satisfactory results, however, nonunion and refracture rates are not negligible. The low-profile "hook" plate is an alternative fixation method that has been promoted to offer improved rotational control at the fracture site, but this remains to be proven. The purpose of this study was to document biomechanical performance differences between this type of plate and a contemporary solid, dual-pitch intramedullary screw in a cadaveric Jones fracture model. Methods: Simulated Jones fractures were created in 8 matched pairs of fresh-frozen cadaveric fifth metatarsals. One bone from each pair was stabilized using an intramedullary TriMed Jones Screw and the other using a TriMed Jones Fracture Plate (TriMed, Inc, Santa Clarita, CA). Controlled bending and torsional loads were applied. Bending stiffness and fracture site angulation, as well as torsional stiffness, peak torque, and fracture site rotation were quantified and compared. Results: Intramedullary screw fixation demonstrated greater bending stiffness and less fracture site angulation than plate fixation during plantar-to-dorsal and lateral-to-medial bending. Torsional stiffness of screw-fixed metatarsals exceeded that of plate-fixed bones at initial loading; however, as rotation progressed, the plate resisted torque better than the screw. No difference in peak torque was demonstrable between fixation methods, but it was reached earlier in specimens fixed with screws and later in those fixed with plates as rotation progressed. Conclusion: In this cadaveric Jones fracture model, intramedullary screw fixation demonstrated bending stiffness and resistance to early torsional loading that was superior to that offered by plate fixation. Clinical Relevance: Although low-profile "hook" plates offer an alternative for fixation of fifth metatarsal Jones fractures, intramedullary screw fixation may provide better resistance to bending and initiation of fracture site rotation. The influence of these mechanical characteristics on fracture healing is unknown, and further clinical investigation is warranted.